2017
DOI: 10.1097/md.0000000000006296
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of the middle and lower cervical vertebral endplates and their components

Abstract: Cervical disc arthroplasty is a common method of treating cervical degenerative disease. However, the footprints of most prosthesis dimensions are obtained from data of Caucasian individuals. Besides, there is a large discrepancy between footprints of currently available cervical disc prostheses and anatomic dimensions of cervical endplates. We aimed to detail the three-dimensional (3D) anatomic morphology of the subaxial cervical vertebral endplate, utilizing high-precision, high-resolution scanning equipment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 28 publications
(34 reference statements)
4
13
0
Order By: Relevance
“…4 ). The values measured on mid-sagittal planes and trends were consistent with the other studies of the measurement of the sub-axial cervical vertebra [ 1 , 4 , 7 ]. There were no significant differences between the values measured by the two observers and observer one (O1).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…4 ). The values measured on mid-sagittal planes and trends were consistent with the other studies of the measurement of the sub-axial cervical vertebra [ 1 , 4 , 7 ]. There were no significant differences between the values measured by the two observers and observer one (O1).…”
Section: Resultssupporting
confidence: 90%
“…Morphometric studies of sub-axial cervical endplates have increased over the past decades [ 1 ], and the main purpose is to provide anatomic data for the design or optimization of the intervertebral instrument and preoperative planning. Dimensional measurements of the endplates have been carried out over a series of entities, from cadaveric vertebrae and radiographic images in the early days of implementing this approach [ 2 , 3 ] and have progressed to include technically advanced methods such as CT and MRI in recent years [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Various morphological studies, as well as the present study, have revealed that the cervical endplate is not simply flat (10,(19)(20)(21); rather, most IEPs are arched (10,21). Although most SEPs are considered relatively flat, they still exhibit a concave depth of 0.39-0.69 mm (19,20).…”
Section: Discussionsupporting
confidence: 52%
“…Various morphological studies, as well as the present study, have revealed that the cervical endplate is not simply flat ( 10 , 19-21 ); rather, most IEPs are arched ( 10 , 21 ). Although most SEPs are considered relatively flat, they still exhibit a concave depth of 0.39-0.69 mm ( 19 , 20 ). Therefore, the flat end of conventional TMCs do not match well with the endplate, leading to a very small contact area and high stress concentration at the TEI ( 4 , 7 , 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the superior approaches of arthrodesis is Trans-pedicular screw. There is a need for detailed anatomical knowledge in the Indian population as the instrumentation involves damage to various vital structures, and also there is a variability in vertebral dimensions amongst different races [12][13][14][15][16][17][18][19] thus causing difficulty in the standardization of measurements. The characteristic of a typical cervical vertebrae is the presence of transversely elongated bodies.…”
Section: Discussionmentioning
confidence: 99%